2006
DOI: 10.1167/iovs.05-1540
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bioerodible Deep Scleral Lamellar Cyclosporine Implant for Uveitis

Abstract: Diffusion of CsA across the sclera from the episcleral space was not a feasible method of drug delivery to the equine eye. However, placing a deep scleral lamellar CsA implant adjacent to the suprachoroidal space was effective in achieving therapeutic ocular drug concentrations and controlling uveitis in horses with ERU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 59 publications
5
104
1
1
Order By: Relevance
“…Those studies have shown that after implantation cyclosporine A can be found in therapeutic concentrations in various ocular tissues . One report by Gilger et al(2006) found no measurable concentration of cyclosporine A in the cornea after suprachoroidal implantation of the drug delivery device. Yet, the results of the study at hand indicate a certain effect against IMMK.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies have shown that after implantation cyclosporine A can be found in therapeutic concentrations in various ocular tissues . One report by Gilger et al(2006) found no measurable concentration of cyclosporine A in the cornea after suprachoroidal implantation of the drug delivery device. Yet, the results of the study at hand indicate a certain effect against IMMK.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Additionally, using an ocular implant also allows for a sustained release of drug into the eye which can improve patient compliance as the frequency of dose is reduced and thus a reduced risk of toxicity. [35] Ocular implants can also prolong therapeutic duration at the site of action compared to other conventional drug delivery methods such as eye drops. [36] The use of ocular implants can overcome the limitation of topical eye drops where drug wastage is an immediate issue.…”
Section: Liposomesmentioning
confidence: 99%
“…In situ gels are a drug delivery system which when administered in a liquid form phase shift into a gel or solid form once reaching the conjunctival cul-de-sac. [39] Despite typically being administered [1,4] ) 2 Ability to modify the rate of release of drug [1,4] 3 Ability to provide a stimuli-sensitive drug release mechanism [1,4] 1 Allow sustained release of drug [35,36] 2 Prolonged therapeutic duration at site of action [35,36] 3 Can overcome limitation of eye drops where drug wastage is an issue [35,36] 1 No blurred vision or irritation with administration [39,40] 2 Prolonged drug retention at desired tissue in the eye [39,41] 3 Decreased frequency of dosing [40,41] 1 Both hydrophilic or lipophilic drugs can be used [32] 2 Increase drug penetration across conjunctival and corneal epithelium [32] 3 Display ability to provide sustained released [32,46] 4 Decreased frequency of dosing [46] Cons 1 Low reproducibility [4,48] 2 Instability of the macromolecules during production stage [4,48] 3 Variable size distribution [4,48] 4 Expensive [4,48] 1 May increase intraocular pressure and induce local systemic adverse effects [38] 2 Inconvenient administration for patient [38] 3 Risk of tissue damage if administered incorrectly [38] 1 Lack of cell specificity [41] 2 Requires intravitreal administration due to poor penetration & specificity [40] 3 Expensive …”
Section: Liposomesmentioning
confidence: 99%
“…This increases the residency time of drug in the episcleral space and increases the concentration in the vitreous and retina compartments. A successful approach to improve the efficiency of transscleral drug delivery was reported in treating the blinding eye disease in horses, equine recurrent uveitis [52] . Here, subconjunctival implants releasing cyclosporine were placed in sub-Tenon's space, and the uveitis progressed unabated.…”
Section: Transscleral Drug Deliverymentioning
confidence: 99%